Digital Literacy and Digital Competence of Selected Filipino Teachers: Basis for a Post-Pandemic Pedagogy - Jhessie Lawaan Abella; Elmer Dela Rosa (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2023)
Objective: The study seeks to provide a thorough description of the teachers' digital literacy (DL) and digital competence (DC) and shine a light on the variables that influence the development of their digital literacies and competence. Method: Comprehensive data collection and analysis from 274 participants were completed. Descriptive and inferential statistics were conducted to accomplish the objectives of this study. Results: It came to light that teachers with less than ten years of experience have higher levels of digital literacy. Pre-service education, having access to ICT resources, and a favorable attitude about using ICT were all strongly associated with DL and DC. The research's essential contribution is its findings affirming the value of DL and DC, which can be utilized to approach new technologies critically and use them as a part of digital pedagogy. Novelty: The critical contribution of the research is the result claiming the positive status of DL and DC, which can be used to approach new tools from a critical pedagogical perspective and apply them as part of digital pedagogy.